2005
DOI: 10.1002/jmv.20454
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity analysis of the hepatitis B virus genome in intrauterine infection

Abstract: There are many factors leading to intrauterine infection with hepatitis B virus (HBV). These factors include viral structure, HBV mutations, HBV DNA level, placenta barrier, immune status of the mother, and susceptibility of the fetus. The purpose of this study was to investigate the possible relationship between intrauterine infection with and HBV mutations of the genome of the virus. In this study, HBsAg-positive mothers were divided into two groups: intrauterine infection group and non-infection group accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
17
1
1
Order By: Relevance
“…The outer primers were HBVS1 and HBVS2 and inner primers were HBVS3 and HBVS4 (25,26). The first and second round amplifications were performed in a total volume of 50 µL, containing 1× reaction buffer, 0.2 mM dNTPs, 1.5 mM MgCl 2 , 0.4 µM of each primer, 0.5 µL of Taq DNA polymerase, and 10 µL of DNA.…”
Section: Nested Pcr For the S Genementioning
confidence: 99%
“…The outer primers were HBVS1 and HBVS2 and inner primers were HBVS3 and HBVS4 (25,26). The first and second round amplifications were performed in a total volume of 50 µL, containing 1× reaction buffer, 0.2 mM dNTPs, 1.5 mM MgCl 2 , 0.4 µM of each primer, 0.5 µL of Taq DNA polymerase, and 10 µL of DNA.…”
Section: Nested Pcr For the S Genementioning
confidence: 99%
“…In our previous studies [14,15] , we analyzed the relationship between intrauterine HBV infection and virus gene heterogeneity by comparing HBV sequences from Fre quency of point mutation: the frequency of patients with a specific mutation divided by the total number of patients from 1 group (numbers of cases with percentages in parentheses). p values were assessed by Fisher's exact test and corrected with the Benjamini-Hochberg method.…”
Section: Discussionmentioning
confidence: 99%
“…HBV DNA was extracted using a commercially available kit (QIAmp DNA blood mini-kit, Qiagen Inc., USA) and then amplified with the high-fidelity PCR System (Roche Corporation) according to the manufacturers' specifications using the following primer pairs: 5 -CGGGATCCCATA-TTCTTGGGAACAAG-3 (nt2826-2844) and 5 -CACTGCAG-GGTTTAAATGTATACCCA-3 (nt839-821) [14] . The PCR conditions were as follows: 5 min at 94 ° followed by 35 amplification cycles of 45 s at 94 ° , 1 min at 60 ° and 2 min at 72 ° .…”
Section: Hbv Pcr Amplification and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…58,68 Recently, several studies have demonstrated the association between genetic polymorphisms and susceptibility of HBV infection. 73,74 Su et al 74 reported fewer mutations in the pre-S and S region of HBV isolated from infants infected in utero. [69][70][71] On the other hand, the interleukin-10 -1082 G allele was associated with reduced HBV intrauterine infection.…”
Section: Intrauterine Transmissionmentioning
confidence: 99%